ANALISIS KEMAMPUAN GURU DALAM PEMBELAJARAN DARING DI SD N 9 RUPAT - Bujang N (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
Learning is essentially the process of interaction between learners and the learning environment coordinated by the teacher. Teachers have difficulty in the development of curriculum in accordance with online learning, learning management, character planting of learners due to limited interaction with learners, as well as limited efforts to empower learners. The implementation of online learning is supported by online learning devices such as smartphones, laptops with adequate connection networks and supported by several applications such as google classroom, video converence, telephone or live chat, zoom or through whatsapp group. The research used was School Action Research (PTS) using kemmis and Mc. Taggart model research designs. This research was conducted at SD Negeri 9 Rupat. The subject of this study was a teacher, the number of teachers as many as 5 people. Two cycles that show the results of an analysis of teacher's abilities with an increased average. Cycle I averaged 33.33%, while in cycle II the average gained 66.66%. These results can be seen from the ability of teachers to use, understand, skill, combine, and develop applications as a means of online learning.